Renal infarction due to ascending aortic thrombus: A case report - Beliz Oztok Tekten; Mustafa Hizal (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2020)
Ascending aortic thrombus is a rare condition that is fatal due to its complications [1]. In this case report, we aim to present a case of renal infarction due to ascending aortic thrombus. A 71-year-old male patient was admitted to the emergency department with chest pain and right-side pain. Physical examination revealed tenderness in the right flank. Thoracic Computed Tomography (CT) angiography was performed, and ascending aortic thrombus and focal parenchymal infarction area in the right kidney were observed in abdominal sections included in the examination.